2017
DOI: 10.1063/1.4995619
|View full text |Cite
|
Sign up to set email alerts
|

Large ferroelectric polarization of TiN/Hf0.5Zr0.5O2/TiN capacitors due to stress-induced crystallization at low thermal budget

Abstract: We report on atomic layer deposited Hf0.5Zr0.5O2 (HZO)-based capacitors which exhibit excellent ferroelectric (FE) characteristics featuring a large switching polarization (45 μC/cm2) and a low FE saturation voltage (∼1.5 V) as extracted from pulse write/read measurements. The large FE polarization in HZO is achieved by the formation of a non-centrosymmetric orthorhombic phase, which is enabled by the TiN top electrode (TE) having a thickness of at least 90 nm. The TiN films are deposited at room temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
179
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(197 citation statements)
references
References 22 publications
15
179
0
1
Order By: Relevance
“…Dopant dependent different elastic properties or crystallization behavior might be two potential origins (see Supporting Information S2) that could give rise to different stress states. [28,29] Theoretical [30][31][32] and first experimental [33][34][35] works have been dedicated to elucidating the role of strain on the enhancement or suppression of the dipole in fluorite-type ferroelectrics (hafnia and zirconia). [25][26][27] The top electrode capping, which was shown to promote the ferroelectricity, has been suggested to be related with a stress effect already in the original publications.…”
Section: Spontaneous Polarization Stress and Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopant dependent different elastic properties or crystallization behavior might be two potential origins (see Supporting Information S2) that could give rise to different stress states. [28,29] Theoretical [30][31][32] and first experimental [33][34][35] works have been dedicated to elucidating the role of strain on the enhancement or suppression of the dipole in fluorite-type ferroelectrics (hafnia and zirconia). [25][26][27] The top electrode capping, which was shown to promote the ferroelectricity, has been suggested to be related with a stress effect already in the original publications.…”
Section: Spontaneous Polarization Stress and Strainmentioning
confidence: 99%
“…According to Batra et al, [31] the FE Pca2 1 phase can be promoted by both compressive hydrostatic and equibiaxial strain in the bc-plane (according to the definitions of a, b, and c used here). [20,[33][34][35] However, deriving a unified picture is not yet possible and a deeper discussion is beyond the scope of this work. However, the energy promotion from the strain was not predicted as sufficient to stabilize the FE Pca2 1 over the monoclinic and nonpolar orthorhombic Pbca phase and thus, an additional destabilization mechanism for these two phases must be assumed.…”
Section: Spontaneous Polarization Stress and Strainmentioning
confidence: 99%
“…The relative amount of the orthorhombic phase and the ferroelectric properties depend on the annealing conditions and film thickness. 3,[6][7][8][9][10][11][12][13] The ferroelectric orthorhombic phase can be also stabilized in epitaxial films. [14][15][16][17][18][19][20][21] In epitaxial films, the orthorhombic phase is generally formed during deposition at high temperature, without need of annealing.…”
Section: Introductionmentioning
confidence: 99%
“…This ratio can be easily realized using common deposition techniques like atomic layer deposition (ALD) with a homogenous concentration throughout the film. 2) The FE properties of HZO films can be achieved at low process temperatures of about 400 °C . This is most likely due to the low crystallization temperature of ZrO 2 compared with other potential high‐k oxides .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that thin HZO films could be crystallized successfully in the desired FE phase by applying rapid thermal annealing (RTA) at 400 °C and even 300 °C for 30 or 60 s. Furthermore, phase transition kinetics were studied (at prior RTA crystallized films) during supplementary annealing at different temperatures and durations to simulate the thermal profile present during the formation of the interconnects, where high‐temperature processes (up to 400 °C) occur several times and last from some minutes to hours.…”
Section: Introductionmentioning
confidence: 99%